Empirical models for predicting the spatial variation of soil thickness and shear strength for landslide susceptibility assessment (Journal of Nepal Geological Society, 2018)
Spatial variation of soil thickness, cohesion and friction angle are crucial in large scale slope stability analysis. However, determination of these parameters is challenging, costly and time consuming. In order to opt out expensive laboratory tests and laborious field investigation, efforts had been done by many researchers to predict these parameters over large areas. In this study, the soil samples and soil thickness data are gathered from 30 sampling boreholes and 60 probed points in an area with Pliocene-Pleistocene geology. The details on slope angle are obtained from the slope map through a processed Digital Elevation Model (DEM) in Geographic Information System (GIS) particularly the ArcGIS software. Slope angles are confirmed in the site through actual measurement using the clinometer. The soil thickness is measured from the ground surface down to the interface of soil and weathered bedrock. The cohesion and friction angle are determined from the direct shear test. Regression analysis is used to establish an empirical modelcorrelating the soil thickness and shear strength parameters with the slope angle. The result revealed that the slope angle has yielded better correlation to the soil thickness than the cohesion and friction angle. The resulting slope angle-soil thickness empirical model is validated from ten different sites with similar geology.